Psychological peculiarities of educational dialogue that influence the effectiveness of the process of forming students' speech competence in learning foreign languages (Pedagogy of Higher and Secondary Education, 2012)
Lapina V. O. Psychological peculiarities of educational dialogue that influence the effectiveness of the process of forming students' speech competence in learning foreign languages.Psychological descriptions of educational dialogue and its features which expose the specific of dialogue organization in educational process, show its possibilities in bringing up personality sphere of students as well as in developing their professionally oriented speech competence in the process of foreign languages learning are considered in the article.
Keywords: educational dialogue; educational activity; psychological descriptions; features; factors; dialogic situation; speech competence; pedagogics of collaboration; reflection